Utószó: Recepció- és kutatástörténeti specimen - Imre, Mihály (Studia Litteraria, 2012)
Western European scholars have widely examined early modern Protestant martyrology since the nineteenth century. German, French, English and Dutch scholars have achieved significant results by applying the cross confessional study of martyrology, a field of research denying strict disciplinary boundaries. In the context of various research projects on cultural memory (Das kulturelle Gedächtnis), recent studies on early modern martyrology have explored how martyrs were used as “sites” of religious and national memory (Erinnerungsorte, les lieux de mémoire), and how these persons were provided as “loci” for ritualized and political modes of remembrance (Erinnerungspolitik, Erinnerungskonkurrenz). This process of commemoration and oblivion also implies the fictionalization of the historical tradition, developed a Protestant culture of martyrs, and eventually created a special narrative of martyrdom. A few research projects have already started to systematically explore the construction of early modern martyrology as a mixture of different religious and national identities, with special attention to the anthropological aspects of the experience of suffering (Leidenserfahrung). The representations of early modern martyrs in several genres, stylistic registers and texts can help us to explore the reasons of their different roles in religious, national, and cultural memory.Protestant martyrology was rejected by the members of the Catholic Church in the sixteenth and seventeenth centuries. This phenomenon was interpreted from a confessional perspective by Petrus Canisius, Laurentius Surius and by other Catholic authors. As a result of the persecution of Hungarian Protestants in the 1670s, several texts were written and published not only in Hungarian, but also in Latin, German, English, Dutch and French. While Hungarian researchers have not focused on early modern Protestant martyrology yet, the present volume tries to facilitate a deeper understanding of martyrdom as a cross confessional and cross-cultural phenomenon, as well as encourage further study.